Vesicular expression and release of ATP from dopaminergic neurons of the mouse retina and midbrain - Ho, Tracy; Jobling, Andrew I.; Greferath, Ursula; Chuang, Trinette; Ramesh, Archana; Fletcher, Erica L.; Vessey, Kirstan A. (Frontiers in Cellular Neuroscience, 2015)
Vesicular nucleotide transporter (VNUT) is required for active accumulation of adenosine tri-phosphate (ATP) into vesicles for purinergic neurotransmission however the cell types that express VNUT in the central nervous system remain unknown. This study characterized VNUT expression within the mammalian retina and brain and assessed a possible functional role in purinergic signaling. Two native isoforms of VNUT were detected in mouse retina and brain based on RNA transcript and protein analysis. Using immunohistochemistry, VNUT was found to colocalize with tyrosine hydroxylase (TH) positive, dopaminergic (DA) neurons of the substantia nigra and ventral tegmental area, however, VNUT expression in extranigral non-DA neurons was also observed. In the retina, VNUT labeling was found to colocalize solely with TH-positive DA-cells. In the outer retina, VNUT-positive interplexiform cell processes were in close contact with horizontal cells and cone photoreceptor terminals, which are known to express P2 purinergic-receptors. In order to assess function, dissociated retinal neurons were loaded with fluorescent ATP markers (Quinacrine or Mant-ATP) and the DA marker FFN102, co-labelled with a VNUT antibody and imaged in real time. Fluorescent ATP markers and FFN102 puncta were found to colocalize in VNUT positive neurons and upon stimulation with high potassium, ATP marker fluorescence at the cell membrane was reduced. This response was blocked in the presence of cadmium. These data suggest DA neurons co-release ATP via calcium dependent exocytosis and in the retina this may modulate the visual response by activating purine receptors on closely associated neurons.